Pogled menedžerjev in zaposlenih na kakovost delovnega življenja v slovenskem hotelirstvu - Šuligoj, Metod (Naše gospodarstvo, 2010)
In the hotel industry, the sociological point of view is equally important as economic and legal points of view. The article provides a general description of 'quality of work life', underscoring its important elements in the hotel industry, such as the relationship between the employees and the guests, the level of autonomy, and work conditions. The empirical part of the article is even more concrete and emphasises four dimensions of the quality of work life: independent decision making, independent problem solving with guests, innovation, and control. Using a bivariate analysis method, it is determined that managers and employees have different perspectives of all dimensions except control.
Keywords: Slovenia; Slovenija; hotelirstvo; managerji; zaposleni; delovno okolje; delovni pogoji